INCORPORATING DIRECTED READING THINKING ACTIVITY (DRTA) TECHNIQUE INTO EXTENSIVE READING CLASS - Rukminingsih, Rukminingsih (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2014)
Abstract: This research focused on incorporating Directed Reading Thinking Activity (DRTA) technique into Extensive Reading to the Fourth semester of English Department in STKIP PGRI Jombang. This research applied a qualitative research in which observation, interview, and documentation employed as data collection techniques. The findings showed that the implementation of data can be combined by several techniques in order to develop the understanding and make the students enjoy, interest, and enthusiasm during teaching learning process.Â ÙÙ Ø¹Ø¨Ø§Ø±ÙØ§ ÙØµÙÙ ÙØ§Ø·ÙÙØ§ Ø©Ø¹Ø³Ø§Ù Ø©Ø¡Ø§Ø±ÙÙØ§ ÙÙ Ø©ÙÙÙØª )DRTA( Ø±Ø®Ø¢ ÙØ±ÙÙØªÙØ§ Ø©Ø¡Ø§Ø±ÙÙØ§ Ø¬Ø§Ø±Ø®Ø¥ Ø¬ÙØ¯ ÙÙØ¹ Ø«ØØ¨ÙØ§ Ø§Ø°Ù Ø²ÙØ±Â ØØ©Ø¸ØÙØ§ÙÙØ§ ÙØ°ÙØ§ ÙØ¹ÙÙÙØ§ Ø«ØØ¨ÙØ§ ÙÙ ÙÙÙØ¨Ø·ØªÙØ§ Ø«ØØ¨ÙØ§ Ø§Ø°Ù .STKIP PGRI Jombang ÙÙ Ø©ÙØ²ÙÙÙØ¬ÙØ¥Ø§ Ø©ØºÙÙØ§ ÙØ³ÙÂ ÙÙØ¨ Ø¹ÙÙØ¬Ø§ ÙÙÙÙ DRTA Ø°ÙÙÙØª ÙØ£ Ø¬Ø¦Ø§ØªÙÙØ§ ØªØ±ÙØ¸Ø£Ù .ØªØ§ÙØ§ÙØ¨ÙØ§ Ø¹Ø¬Ù ØªØ§ÙÙÙØª ÙØ¹ Ø©ÙØ¯Ø®ØªØ³ÙÙØ§ ÙØ¦Ø§Ø«ÙÙØ§Ù ØØ©ÙØ¨Ø§ÙÙÙØ§ÙÙÙØ¹ØªÙØ§Ù ÙÙÙØ¹ØªÙØ§ Ø©ÙÙÙØ¹ Ø¡Ø§ÙØ«Ø£ Ø³Ø§ÙÙØØ§Ù ØØ©Ø¯Ø¦Ø§ÙÙØ§Ù ØØ¨ÙØ§Ø·ÙØ§ Ø¹ØªÙØªÙØ§ ÙØ¹Ø¬Ù ÙÙØ§ÙØªÙØ§ Ø±ÙÙØ·Øª ÙØ¬Ø£ ÙÙ ØªØ§ÙÙÙØª Ø©Ø¯Ø¹